Production of Destruxins by Coprotrophic Beauveria feline No. 7 Strain - M. V. Bibikova; T. O. Puzhevskaya; A. N. Danilenko; I. A. Spiridonova; G. V. Zatonsky; A. V. Aleksandrova; A. V. Katlinsky (Антибиотики и Химиотерапия, 2020)
Beauveria feline No. 7 strain was isolated from the shrewmouse wool and characterized by production of a complex of destruxins cyclodepsipeptides. The strain was shown to produce significant quatities of destruxin B and pseudodestruxin C. The destruxins were found to be able to inhibit formation of biofifms by Pseudomonas aeruginosa ATCC 27833.